Restorative Justice Approach to the Juvenile Criminal Justice System in Indonesia - Saputra, Ade Rizki; Gunati, Mira; Haryono, Tri Agus; Kurniati, Yeti; RAS, Hernawati (Formosa Journal of Sustainable Research, 2024)
The restorative justice (RJ) approach in the juvenile criminal justice system in Indonesia offers an alternative solution that focuses on the rehabilitation and social reintegration of children in conflict with the law. This article discusses the implementation of RJ, the challenges faced, and solutions that can be sought to overcome these obstacles. Using descriptive qualitative methods, this research highlights the importance of training for legal officers, adequate resource allocation, outreach campaigns, and the formation of effective networks as strategic steps in strengthening RJ in Indonesia